A kinematical analysis of the polishing processes of hard magnetic disk substrate. (February 2014) - Lu, Yushan; Shu, Qilin; Wang, Jun; Liu, Yueming
This article presents a comprehensive study of material removal distribution in the polishing processes using kinematical simulation and experimental validation. The equations of material removal rate and dimensionless distribution of material removal volume are developed based on the randomly distributed abrasive grains and the kinematical–geometrical parameters of the polisher. These equations are used to generate the motion paths of abrasive grains to describe their cutting trajectories and the dimensionless distribution of material removal volume in three parameters (the crank length, rotational speed of the crank and rotational speed of the carrier). Then, the corresponding experiments are carried out to validate the numerical results. Measuring the material removal thickness of the polished hard disk substrates, the results are approximately consistent with the numerical trends. According to the demand of the polished surface, choosing reasonable geometrical and kinematical parameters can improve the machining efficiency and accuracy.